A clinico-pathological study of lichenoid tissue reactions/interface dermatitis - Dixit, Deepti; Vernekar, Sunita S.; Giriyan, Sujata S. (International Journal of Research in Medical Sciences, 2019)
Background: Lichenoid tissue reaction/Interface dermatitis (LTR/ID) refers to a number of clinically diverse, poorly understood and relatively uncommon inflammatory skin diseases. This study was done to understand the histopathological features of lichenoid tissue reactions in skin biopsies and to assess the concordance and disparity between the clinical and histopathological diagnosis of variants of the same. Methods: It was a 3½ years study from January 2014 to June 2017 in the department of Pathology, KIMS, Hubballi. The present study included skin biopsies of clinically diagnosed and suspected cases and histologically diagnosed cases of LTRs. Skin biopsies received were routinely paraffin processed and H&E stained to study the microscopic features. Results: Out of 166 skin biopsies studied, 148 were histologically confirmed as LTR with majority being of lichen planus (LP) (91.22%). Classical lichen planus was the most common variant of lichen planus among lichen planus cases. Male:female ratio was 1.2:1. Clinico-pathological concordance was seen in 88.55% of the cases. Conclusions: Though definite diagnosis can be made on histopathological examination, size of specimen, site of biopsy, nature and depth of biopsy, quality of sections, treatment history and inter-observer variation (both clinically and histologically) should be kept in mind which may lead to clinicopathological discordance.